Health-Related Quality of Life and mental health of families with children and adolescents affected by rare diseases and high disease burden: the perspective of affected children and their siblings - Silke Wiegand-Grefe; Anna Liedtke; Lydia Morgenstern; Antonia Hoff; Anikó Csengoe-Norris; Jessika Johannsen; Jonas Denecke; Claus Barkmann; Benjamin Grolle; Anne Daubmann; Karl Wegscheider; Johannes Boettcher (BMC, 2022)
Abstract Background Advances in genetic and pharmaceutical technology and pediatric care have enabled treatment options for an increasing number of rare diseases in affected children. However, as current treatment options are primarily of palliative nature, the Health-Related Quality of Life (HRQoL) and mental health of this impaired population and their siblings are of increasing importance. Among children and adolescents with rare diseases, those who are technology-dependent carry a high disease burden and are selected as the target population in our study. In a cross-sectional observational design, the children's HRQoL was assessed with the DISABKIDS (DCGM-37) as well as KIDSCREEN-27, while mental health was assessed with the Strengths and Difficulties Questionnaire (SDQ) by both the affected children, their parents, and siblings. Results Results of the study sample were compared to normative data. Affected children scored significantly lower than the norm on almost all HRQoL subscales as reported by parent and child. From the parental perspective, more mental health subscales were significantly impaired compared to the child's perspective. Siblings showed no impairment in HRQoL as well as significantly fewer behavioral problems and higher prosocial behavior regarding their mental health compared to the norm. Conclusion Children and adolescents with rare diseases seem particularly impaired in social and emotional aspects of HRQoL and mental health. Interventions may focus primarily on promoting social skills, fostering prosocial behavior and peer relationships.